Statewide Seasonal Variations of Infections Within the Intensive Care Unit Among the Trauma Population. Issue 4 (April 2021) - Clark, Jason M.; Durrani, Hamza; Hagan, Josh D.; Watson, Carrie; Richards, Winston T.; Taylor, Dana; Ang, Darwin N.
Background: Infections within intensive care unit (ICU) are a persistent problem among the critically ill. Viral pneumonias have already been established as having a season variations. We attempt to evaluate the seasonal variations of pneumonia among the traumatically injured and the critically ill. Materials and Methods: A retrospective cohort study among traumatized patients admitted from 1997 to 2017 to an ICU within the state of Florida was performed who were diagnosed with pneumonia. A multivariate regression analysis was performed to adjust for confounders. Time periods were divided into seasons: summer, winter, spring, and fall. A subset analysis of geriatric patients (>65 years) was also performed. Results: A total of 869 553 patients were identified. The most common viral infection was influenza with adenovirus the least. The most common bacterial pneumonia was Staphylococcus aureus with Bordetella pertussis the least. Pneumonias had a seasonal variation. Compared to summer, winter had a higher likelihood of pneumonia overall (Adjusted Odds Ratio (AOR)1.13). This was seen in the spring (AOR 1.04) but not in fall (AOR 1.00). Viral infections were more pronounced (AOR 3.79) in all other seasons, while bacterial showed increased likelihood during winter (AOR 1.05). In geriatrics, pneumonia was again more likely in the winter (AOR 1.22) with both viral and bacterial infections being more pronounced during winter (AOR 4.79, AOR 1.09). Discussion: Pneumonias are seen more frequently within the ICU during the winter for the traumatized patient. This held true with the critically ill geriatric population as well. This effect was observed in both viral and bacterial pneumonias.